Studi Analisis Kontrastif Padanan Peribahasa Arab dan Inggris Perspektif Hermeneutika Budaya - Lukman Fajariyah (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This paper discusses the equivalent of Arabic proverbs and English proverbs through a study of contrastive analysis. Contrastive analysis is a method that plays an important role in linguistic analysis whether it is a comparison between two or more languages to explore similarities and differences between the two languages. This type of research is a qualitative descriptive study using a hermeneutic and cultural communicative approach. The author uses this hermeneutic approach to find the meaning of the interpretation of the Arabic proverbial text and the English proverb. Meanwhile, the communicative culture approach is used as an attempt to translate the meanings of symbols of two or more cultures that are reflected in the literary text, then the two are contrasted. The implicit cultural value can be found in the communication process through the terms found in the translation and equivalent of the proverb text, which can be in harmony with the original meaning of the two. The findings in this study are that the application of contrastive analysis has shown the equivalent and appropriate meaning and function represented by Arabic and English proverbs about patience, determination, indiscipline, youth, and truth. So this analysis has implications for understanding communication in social life.